1990
DOI: 10.1159/000276114
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Events in Experimental Otitis Media Models: A Comparative Study

Abstract: The vascular leakage and components of middle ear effusion (MEE) were determined and compared in various experimental otitis media models in the rat: purulent otitis media (POM); serous otitis media (SOM); mucoid-like otitis media (MOM); stimulating the external auditory canal with a 14 °C airstream and vagotomy. When the Evans blue technique was used, all otitis media models exhibited a significant increase in middle ear vessel permeability. The MEEs contained numerous PMNLs, except for animals stimulated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a study of specific pathogen-free rats, Goldie et al [4] found that obstruction of the eustachian tube did not lead to the development of mucoid effusion in the middle ear cavity, unless there was concomitant or prior challenge to the middle ear cleft. This challenge was thought to be related to bacterial infection in the middle ear and stimulation of the mucin metabolism of the mucosa.…”
mentioning
confidence: 99%
“…In a study of specific pathogen-free rats, Goldie et al [4] found that obstruction of the eustachian tube did not lead to the development of mucoid effusion in the middle ear cavity, unless there was concomitant or prior challenge to the middle ear cleft. This challenge was thought to be related to bacterial infection in the middle ear and stimulation of the mucin metabolism of the mucosa.…”
mentioning
confidence: 99%
“…The origin of the SIgA coating the bacteria in the present study must be plasma cells located in the mucous membrane of the MEC, as SIgA is synthesized locally (Tomasi, 1972;Mogi et al, 1974). IgG, on the other hand, is supplied to the purulent MEE by vascular leakage (Ogra et al, 1974;Goldie et al, 1990). It is noteworthy that no SIgA-coated bacteria were found in patients 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Hellstrom et al (2) showed that intrabullar inoculation of one dose of pneumococcus, followed 2 weeks later by Eustachian tube obstruction (ETO), induced accumulation of thick uid in the middle ear cavity, suggesting that multiple factors are involved in the development of otitis media with mucoid effusion. In speci c pathogen-fre e rats, ETO alone rarely induced accumulation of thick uid unless there was a concomitant injury to the middle ear (3). This suggests that an initial insult to the middle ear cleft is important for the production of thick effusion in the middle ear cavity.…”
Section: Introductionmentioning
confidence: 99%